A dose escalation and pharmacodynamic study of triapine and radiation in patients with locally advanced pancreas cancer - Martin, Ludmila Katherine (2012)
PURPOSE: Triapine (Vion Pharmaceuticals), a novel inhibitor of the M2 subunit of ribonucleotide reductase (RR), is a potent radiosensitizer. This NCI/CTEP-sponsored phase I study assessed the safety/tolerability of triapine in combination with radiation (RT) in patients with locally advanced pancreas cancer (LAPCA). METHODS AND MATERIALS: We evaluated 3 dose levels of triapine (24 mg/m(2), 48 mg/m(2), 72 mg/m(2)) administered with 50.4 Gy of RT in 28 fractions. Patients with LAPCA received triapine thrice weekly, every other week during the course of RT. Dose-limiting toxicity (DLT) was assessed during and for 4 weeks following completion of RT. Dynamic contrast enhanced (DCE)-MRI and serum RR levels were evaluated as potential predictors for early response. RESULTS: Twelve patients were treated. Four patients (1 non-evaluable [NE]) were enrolled at dose level 1 (DL1), three patients at DL2, and five patients (2NE) at DL3. No DLTs were observed and the MTD was not reached. Two patients (17%) achieved PR and 6 patients (50%) had SD. One patient underwent R0 resection following therapy. 92% of patients (100% on DL3) experienced freedom from local tumor progression. 75% of patients who eventually progressed developed metastases without local progression. RR levels did not appear to predict outcome. In 4 patients with available data, DCE-MRI may predict early response or resistance to therapy. CONCLUSION: The combination of triapine at 72 mg/m(2) three times weekly every other week and standard RT is tolerable with interesting activity in patients with LAPCA.